Respuesta :
Step-by-step explanation:
3(2-x)=9
this is the answer to the statement
The expression three times the quantity two decreased by x is nine is - 1
A quantity two decreased by x can be expressed thus :
- (2 - x)
Multiplying the quantity by 3 :
- 3(2 - x)
The expression can be written Mathematically as thus : 3(2 - x) = 9
The expression can be expanded further as :
3(2 - x) = 9
6 - 3x = 9
Collect like terms
-3x = 9 - 6
-3x = 3
x = (3 ÷ -3)
x = - 1
Therefore, the expression equates to - 1
Learn more :https://brainly.com/question/18796573